Mass spectrometry‐based proteomics reveals the distinct nature of the skin proteomes of photoaged compared to intrinsically aged skin. (8th April 2019) - Newton, V.L.; Riba‐Garcia, I.; Griffiths, C.E.M.; Rawlings, A.V.; Voegeli, R.; Unwin, R.D.; Sherratt, M.J.; Watson, R.E.B.
Abstract: Objective: With increasing age, skin is subject to alterations in its organization, which impact on its function as well as having clinical consequences. Proteomics is a useful tool for non‐targeted, semi‐quantitative simultaneous investigation of high numbers of proteins. In the current study, we utilize proteomics to characterize and contrast age‐associated differences in photoexposed and photoprotected skin, with a focus on the epidermis, dermal–epidermal junction and papillary dermis. Methods: Skin biopsies from buttock (photoprotected) and forearm (photoexposed) of healthy volunteers (aged 18–30 or ≥65 years) were transversely sectioned from the stratum corneum to a depth of 250 μm. Following SDS‐PAGE, each sample lane was segmented prior to analysis by liquid chromatography‐mass spectrometry/mass spectrometry. Pathway analysis was carried out using Ingenuity IPA. Results: Comparison of skin proteomes at buttock and forearm sites revealed differences in relative protein abundance. Ageing in skin on the photoexposed forearm resulted in 80% of the altered proteins being increased with age, in contrast to the photoprotected buttock where 74% of altered proteins with age were reduced. Functionally, age‐altered proteins in the photoexposed forearm were associated with conferring structure, energy and metabolism. In the photoprotected buttock, proteins associated with gene expression, free‐radical scavenging, protein synthesis and protein degradation were most frequently altered. Conclusion: This study highlights the necessity of not considering photoageing as an accelerated intrinsic ageing, but as a distinct physiological process. Abstract : In this study, we investigated the impact of ageing and light on the proteomes of skin collected at photoexposed and photoprotected sites. Although most of the altered proteins in skin from aged individuals were higher in abundance than in skin from younger individuals, in the photoprotected buttock the majority of the altered proteins were reduced with age. Differences in the functions of altered proteins between photoprotected and photoexposed sites also suggest that the nature of photoageing in skin may be very different and perhaps distinct from non‐photoageing.